Price Dynamics in the US Market for Apparel Imports: Impact of Quota Elimination under the Agreement on Textiles and Clothing and Safeguard Restrictions on the People's Republic of China - William E. James; Juan Paolo Hernando (Asian Development Bank (ADB), 2008)
C. Peter Timmer writes about the causes of high food prices, focusing on staple grains - rice in particular - and edible oils. He shows that although food prices have come down from the spikes of early 2008, they are likely to remain higher than they were in early 2007 for years to come. The paper explores the implications for policy and includes a technical appendix that provides the analytical framework of this analysis.
hdl:11540/1766
Keywords: 330; Import; Bekleidung; Importquote; USA; China